(untitled) (Academia Science Repository, 2023)
This article explores the lexical and grammatical transformations that occur during the process of translation. The article begins by discussing the differences between lexical and grammatical transformations and their importance in translation. It then examines the various types of lexical and grammatical transformations that can occur, including transliteration, lexical borrowing, word order changes, and tense shifts. Additionally, the article examines the role of technology in facilitating lexical and grammatical transformations in translation, including machine translation and translation memory tools.